(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Web applications play a vital role in every modern organization. But, if your organization does not properly test and secure its web apps, adversaries can compromise these applications, damage business functionality, and steal data. Most of the web application contains security vulnerabilities which enables attacker to exploit them and launch attack. As a result of attacks confidentiality, integrity and availability of information are lost. Web applications provide end users with client access to server functionality through a set of Web pages. . In This paper, we will briefly introduce the concept of Web application and server exploitation through SOL injection attack and the realization process of SQL injection attack. On this basis we will also describe how to detect SQL injection attacks. We will use various tools but the main tool is Kioptrix3 which will be used as a target machine. Keywords: VMware, Nmap, Kioptrix3, SQL injection, Vulnerabilities, Web application and Exploit.